Uncommon presentation of an intraosseous squamous cell carcinoma - da-Silva, Leorik Pereira; Gonzaga, Amanda Katarinny Goes; Castro-Nóbrega, Luciana Eloisa da Silva; Germano, Adriano Rocha; Costa, Antonio de Lisboa Lopes (Journal of Oral Diagnosis, 2018)
Primary intraosseous squamous cell carcinoma (PIOSCC) is a rare type of cancer, which commonly arises in the jaw without attachment to the oral mucosa epithelium and presumably develops from remnants of odontogenic epithelium or from odontogenic cysts and odontogenic benign tumors. We report here a case of a 49-year-old male patient who presented pain in the teeth 44 and 45 region. Radiographic examination revealed a small radiolucent and well circumscribed lesion, however, histopathological examination revealed a PISCC. The clinical and radiographic presentation of this tumor can be variable and nonspecific, and even small osteolytic lesions in the gnathic bones can be considered as differential diagnosis of malignant neoplasms of odontogenic origin. Incisional biopsy is fundamental to lead to early diagnosis and indicate appropriate treatment to optimize the prognosis of these cases.